Li2(Se2O5)(H2O)1.5·CuCl2, a salt-inclusion diselenite structurally based on tetranuclear Li4 complexes. Issue 23 (20th May 2020) - Markovski, Mishel R.; Siidra, Oleg I.; Charkin, Dmitri O.; Vladimirova, Victoria A.; Tsirlin, Alexander A.; Grishaev, Vasili Yu.
Abstract : A new lithium copper diselenite chloride hydrate, Li2 Se2 O5 (H2 O)1.5 ·CuCl2, was prepared from aqueous solution. Abstract : A new lithium copper diselenite chloride hydrate, Li2 Se2 O5 (H2 O)1.5 ·CuCl2, was prepared from aqueous solution. Its unique 2D structure can be interpreted as Li2 Se2 O5 (H2 O)1.5 layers with CuCl2 hosts embedded in the interlayer space, and be considered halfway between the salt-inclusion and host–guest structures. The CuO2 Cl4 octahedra form chains similar to those in CuCl2 ·2H2 O, yet water molecules are coordinated exclusively to Li + while Se2 O5 2− and Cl − bridge Li + and Cu 2+ . The complexity of the structure is likely responsible for both very long pre-crystallization time and non-existence of the corresponding bromide analogue. Despite the relatively long Cu⋯Cu separations, the compound exhibits weak ferromagnetic interactions along the chains of CuO2 Cl4 octahedra.